The effect of equalization of public health services on the health China's migrant population: Evidence from 2018 China Migrants Dynamic Survey - Su, BinBin; Wu, Yu; Yihao, Zhao; Chen, Chen; Panliang, Zhong; Zheng, Xiaoying (Frontiers in Public Health, 2023)
Objectives China has implemented an equalization of public health Services policy for the migrant population in 40 pilot cities since 2013. The main purpose of this study was to explore the health impact of the equalization of public health services on China's migrant population. Methods Using the China Migrants Dynamic Survey (CMDS), we included 152, 000 migrants aged 15 years or over in 2018. Standardized questionnaires were used to collect socio-economic information and self-reported health status. The Associations between equalization of public health services and health status were estimated using the ordered probit model and Propensity Score Matching (PSM) methods. Results Equalization of public health Services had a significant positive impact on the health of the Chinese migrant population (β=0.033, P<0.001). Compared to the groups who were the provincial migrations, males, having a higher-than-average income, aged 15-69 years old and living in urban areas, the equal access to public health services had shown more significant positive effects on the groups who were inter-provincial migration(β=0.055, P<0.001), females(β=0.055, P<0.001), having low-income(β=0.077, P<0.001), aged over 60 years old(β=0.191, P<0.001) and living in rural areas(β=0.038, P<0.001). Conclusions and Implications Our findings confirmed the positive health effect of the equalization of public health Services on the migrant population in China. And we recommend that it is necessary to further promote the practices and experiences of the pilot cities for the equalization of public health services. First, strengthen health education and improve the health literacy of the migrant population. Second, increase the financial investments to expand service coverage and promote the quality of public health services and equality among regions. Last, strengthen the information-based management of the migrant population and prevent and control infectious diseases.